Corpo e (des)colonialidade na educação física: histórias de vida e formação docente de professores da rede municipal de Juazeiro do Norte, CE - Simões Neto, José de Caldas (Universidade do Vale do Rio dos Sinos, 2025)
This study aims to investigate the relationship between (de)coloniality and conceptions about the body based on the analysis of the life trajectories, initial training and teaching practices of Physical Education teachers in the municipal school system of Juazeiro do Norte - CE. The thesis addresses how (de)coloniality can help to value body knowledge and practices, promoting a more holistic and integrative view of the body that respects cultural diversity in training and in the school curriculum. The methodology used was based on life history, through autobiographical narrative interviews, a method that allowed us to analyze how life trajectories, training and teaching practices influence the conception of the body in Physical Education. The results reveal that, although conceptions about the body are influenced by persistent colonial structures, especially in schools, there is also evidence of resistance and transformation of teachers' pedagogical practices. The data collection revealed that teachers are engaged in inclusive and critical pedagogical practices, challenging traditional norms and promoting a more equitable Physical Education. However, the teachers who participated in the study stated that they are still dealing with practical challenges and structural resistance, especially with the curriculum. The narrative interviews conducted reveal a diverse panorama of (de)colonial approaches in Physical Education and their implications for their life stories. While some teachers demonstrate an explicit commitment to inclusion and criticism of power structures, others face obstacles that limit the implementation of these practices, either due to their experiences in training or due to professional performance involved in Eurocentric influences. The study suggests the need for public policies and training programs that support (de)colonial pedagogical practices, valuing cultural diversity and promoting Physical Education that contributes to social transformation based on the epistemologies of the South.

Este estudio tiene como objetivo investigar la relación entre la (des)colonialidad y las concepciones sobre el cuerpo a partir del análisis de las trayectorias de vida, formación inicial y prácticas docentes de profesores de Educación Física en la red municipal de Juazeiro do Norte - CE. La tesis aborda cómo la (des)colonialidad puede ayudar a valorar los conocimientos y prácticas corporales, promoviendo una visión más holística e integradora del cuerpo que respete la diversidad cultural en la educación y en el currículo escolar. La metodología utilizada se basó en la historia de vida, a través de entrevistas narrativas autobiográficas, método que permitió analizar cómo las trayectorias de vida, las prácticas formativas y docentes influyen en la concepción del cuerpo en la Educación Física. Los resultados revelan que, si bien las concepciones sobre el cuerpo están influenciadas por estructuras coloniales persistentes, especialmente en las escuelas, también hay evidencia de resistencia y transformación de las prácticas pedagógicas de los docentes. La producción de datos identificó que los docentes participan en prácticas pedagógicas inclusivas y críticas, desafiando las normas tradicionales y promoviendo una Educación Física más equitativa. Sin embargo, los docentes que participaron en la investigación afirmaron que aún enfrentan desafíos prácticos y resistencias estructurales, especialmente en el currículo. Las entrevistas narrativas realizadas revelan un panorama diverso de los enfoques (de)coloniales en Educación Física y sus implicaciones en sus historias de vida. Si bien algunos docentes demuestran un compromiso explícito con la inclusión y la crítica a las estructuras de poder, otros enfrentan obstáculos que limitan la implementación de estas prácticas, ya sea por sus experiencias en formación o por su práctica profesional involucrada en influencias eurocéntricas. El estudio sugiere la necesidad de políticas públicas y programas de formación que apoyen prácticas pedagógicas (de)coloniales, valorando la diversidad cultural y promoviendo una Educación Física que contribuya a la transformación social basada en epistemologías del sur.
Keywords: Corpo; Educação Física; (Des)colonialidade; História de vida; Body; Physical education; (De)coloniality; Life's history; Teachers; Cuerpo; Educación Física; (Des)colonialidad; Maestros; ACCNPQ::Ciências Humanas::Educação